Lead Exposure and Intellectual Function: Findings from Primary School Children in Bangladesh (Bangladesh Journal of Medical Science, 2012)
Backgrounds: About 120 million people around the world are overexposed to lead which is neurotoxic and 99 percent of the most severely affected children are in the developing world including Bangladesh. Methods and Materials: The present cross-sectional ecological study was carried out to explore the impact of lead poisoning on the intelligence level among 84 primary school children of a school of Bangladesh, aged between 8 and 14 years from September 2010 through January 2011. The research instrument was an interviewer questionnaire, questionnaire for IQ test and assessment of blood lead level (inductively-coupled plasma mass spectrometry with collision/reaction cells) of the study subjects after obtaining permission from their parents and the school authority. Results: Data were cross-checked and frequency distribution and association using chi-square test was accomplished. Background information depicted majority (69.1%) of the children aged10-11 years (mean = 10.25 ±1.177 yrs), female (51.2%), parents having primary level of education or below (73.8% in case of father and 77.4% in mother) and from lower socioeconomics (78.6% earned BDT 10,000 or below per month). Among all, majority (56%) were found to be moron, 27.4% in borderline, while 8.3% were imbecile with the same proportion with normal level. By their blood lead level. Majority (70.2%) had blood lead level up to 10 microgram/dl and the rest (29.8%) had more than 10 microgram/dl. Though no statistically significant association was found between IQ level of the children and their blood lead level (p>0.05), the health problems found among the respondents as abdominal pain (53.57%), impatience (14.29%), nausea (10.71%) and all other problems (loss of concentration to study, ear problem, anorexia and loss of weight) amounting for 21.43% are suggestive of chronic lead poisoning. Conclusion:Further studies in large scale with larger samples including comparative studies of inter-industrial areas have been strongly recommended. DOI: http://dx.doi.org/10.3329/bjms.v11i4.12599 Bangladesh Journal of Medical Science Vol. 11 No. 04 Oct12